Combination immunosuppressant therapy and lupus nephritis outcome: a hospital-based study. (April 2019) - Chen, Y M; Hung, W T; Liao, Y W; Hsu, C Y; Hsieh, T Y; Chen, H H; Hsieh, C W; Lin, C T; Lai, K L; Tang, K T; Tseng, C W; Huang, W N; et al.
Lupus nephritis (LN) is the leading cause of mortality in lupus patients. This study aimed to investigate the treatment outcome and renal histological risk factors of LN in a tertiary referral center. Between 2006 and 2017, a retrospective observational study enrolled 148 biopsy-proven LN patients. After propensity score matching, 75 cases were included for further analysis. The classification and scoring of LN were assessed according to the International Society of Nephrology/Renal Pathology Society. Treatment response was evaluated by daily urine protein and urinalysis at two years after commencing induction treatment and the development of end-stage renal disease (ESRD). In total, 50.7% patients achieved complete remission (CR) or partial remission (PR), while 49.3% patients were categorized as nonresponders. Therapeutic responses in terms of CR/PR rates were associated with Systemic Lupus Erythematosus Disease Activity Index scores (odds ratio (OR): 1.34, 95% confidence interval (CI): 1.12–1.60, p  = 0.001). Moreover, higher baseline creatinine levels (hazard ratio (HR): 2.10, 95% CI: 1.29–3.40, p  = 0.003), higher renal activity index (HR: 1.30, 95% CI: 1.07–1.58, p  = 0.008) and chronicity index (HR: 1.40, 95% CI: 1.06–1.85, p  = 0.017) predicted ESRD. Among pathological scores, cellular crescents (HR: 4.42, 95% CI: 1.01–19.38, p  = 0.049) and fibrous crescents (HR: 5.93, 95% CI: 1.41–24.92, p  = 0.015) were independent risk factors for ESRD. In conclusion, higher lupus activity was a good prognostic marker for renal remission. Renal histology was predictive of ESRD. Large-scale prospective studies are required to verify the efficacy of mycophenolate in combination with azathioprine or cyclosporine in LN patients.